Kesulitan Akses Pelayanan Kesehatan, Kurangnya Pengetahuan dan Sikap Negatif Tentang Bahaya Pertolongan Persalinan Oleh Dukun - Linda Andri Mustofa; Nurjannah Nurjannah (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2022)
Abstract Delivery assistance by traditional birth attendants causes various problems and the main cause of the high maternal and infant mortality rate is due to the lack of proper attention to safety, hygiene and delivery assistance mechanisms so that various complications can occur which can lead to death. Delivery by traditional birth attendants in Maluku Province is a problem that must be handled appropriately by taking into account the influencing factors. This study aims to describe the causes of the selection of birth attendants between traditional birth attendants and health workers based on the affordability of access to health services, knowledge and attitudes of pregnant women. The quantitative research method with a descriptive research design was carried out on September 5-11 October 2021. The population of all third trimester pregnant women in the working area of the Hitu Health Center, Central Maluku Regency with a total sample of 50 pregnant women with total sampling. The research variables are the affordability of access to health services, knowledge and attitudes. The data collection instrument used a questionnaire whose results were analyzed using a frequency distribution and presented in the form of a bar chart. The results showed that from 50 respondents, 39 respondents (78%) chose to give birth assisted by a traditional birth attendant with the causes of difficulty in accessing health services, lack of knowledge and negative attitudes about the dangers of delivery assistance by non-health workers, each of which was 26 respondents (67%). To be able to change the choice of birth attendant by health workers, it is necessary to have good knowledge and a positive attitude towards the dangers of childbirth assistance by traditional birth attendants and guarantee the ease of accessing delivery services by health workers. The need for cooperation between the government and the local health office in paying attention to the affordability of access to health services as well as providing effective communication and education as well as positive support for health workers for third trimester pregnant women. Keywords: access to health services, knowledge, attitudes, pregnant women, traditional birth attendant